Studi Kelayakan Pengembangan Bisnis Bengkel Motor Henry - Ciputra Darmawan (Jurnal Manajemen Maranatha, 2016)
The aim of this study is to increase Henry workshop business scale and service capacity with business planning strategies in terms of market and marketing aspects, technical aspects / operations, human resource aspects and financial aspects.Some of the strategic plan that will be implemented based on the design of the four business aspects including the renovation and expansion of business premises workshop , procurement of equipment and supplies complete workshop ,additionalservices and products are completely , procurement regular promotion, warranty service and training and development HR continuously. Based on the business plan of the Henry's workshop investment for Henry’s workshop that will yield thepayback period for 2 years and 9 months, the project NPV of Rp 423,112,375.00 , as well as the value of MIRR is 58 % . The conclusion of this business plan is the development that will be done by Henry’s workshop very feasible to be implemented with the conditions of competition in the business today and in thefuture.Keywords: Market and marketing, technical / operations , human resources , finance , feasibility